Fanconi Syndrome induced by the use of Tenofovir in co-infected person HIV-multiresistant Hepatitis B virus - Planello, Jéssica Freitas; Marcelino, Daniela Chinelato; Cypriani, Rafael; Souto, Bernardino Geraldo Alves (ABCS Health Sciences, 2016)
Introduction: HIV-HBV coinfection is common and Tenofovir (TDF) is the drug of choice because it acts against both viruses at the same time. However, about 1% of cases can induce Fanconi Syndrome, leading to kidney failure. Case report: On an HIV-HBV co-infected man, with controlled HIV replication, Hepatitis B virus was resistant to all available drugs, except TDF. Twenty-two months after antiretroviral treatment compound with that drug, which controlled both viruses’ replication at the same time, he developed renal insufficiency with loss of absorbable solutes at proximal convoluted tubule, diagnosed as Fanconi Syndrome induced by TDF. Facing the dilemma of suspending the TDF for preserving the kidney and to allow the replication of the HBV, or to keep the TDF for preserving the liver and to accept the renal degeneration, we chose to balance the treatment according to the best possible equilibrium between HBV replication and kidney preservation, adjusting the posology of medications according to clinical and laboratorial indicators of liver risk and renal function. Conclusion: The only therapeutic option currently available to coinfected people by HIV-HBV who develop renal failure by the TDF consists on adjustment of the dose of the TDF according creatinine clearance, symptomatic treatment, replacement of urinary losses which have metabolic impact, and clinical and laboratory monitoring of the HIV infection, Hepatitis B, Renal insufficiency and Bone remodeling.